Effective Administrative on Early Childhood Education for Primary Schools under the Basic Education Commission Offices in the Northeast - Nilsawang, Peddao; Steannoppakao, Pornthep; Pheasa, Akkaluck (Dhammathas Academic Journal, 2022)
The objective of this research is to study the components of effective administrative on early childhood education for primary schools under the basic education commission offices in the northeast. This research is a documentary research by studying both the main component and the sub-component of 39 research papers related to effective administrative on early childhood education, interviewing 7 experts and studying 3 outstanding schools to synthesize the components of effective administrative on early childhood education. The research instruments consisted of a document analysis form and a semi-structured interview form and analyze the data by content analysis. The research result finds that: There are 5 main components and 19 sub-components of effective administrative on early childhood education: 1) management consist of 5 sub-components 2) participation consist of 3 sub-components 3) early childhood experience consist of 4 sub-components 4) early childhood development consist of 4 sub-components and 5) curriculum and course administration consists of 3 sub-components.